Factors influencing fulfillment of zakat on income through online payment public and private workers / Siti Faralia Johary - Johary, Siti Faralia (2017)
Zakat is one of the five pillars of Islam. Al Quran and Al Hadith said that zakat is one of the pillars of Islam and Muslims are obliged to pay zakat. Zakat payment through online has become one of the method where payer can contribute their zakat. In 2015, total payment of zakat through online has increase from RM 3 1,9 17,772 to RM 39, 162,283. Due to constraints facing by Muslims that works in public and private areas, such as busy with works and do not have the opportunity to visit zakat's counter or the 'amil' (Zakat's Collector), the online payment zakat had been introduced. The zakat payment through online is much easier than dealing with traffic congestion, parking search and busy demand of works. The general objective of this study is to determine the factors that influencing fulfilment of zakat on income through online payment among public and private workers. The dependent variable the factors influencing fulfilment of zakat on income through online payment among public and private workers. The independent variables are usefulness, ease to use, quality of Internet connection and trust. The data had been collected using a questionnaire and a secondary data such as journal, internet and magazines. In order to assess and evaluate the data, public and private workers will be choose. This study used quantitative survey that based on primary data in survey with quantitative analysis procedure that are numerical data, graphs and statistics using Statistical Package for Social Science (SPSS) program. From the finding and analysis, it can be concluded that two independent variables which is usefulness has significant relationship and supported by past researcher Baker-Eveleth & Stone, 2016) and quality of Internet connection shown a significant relationship and supported by past researcher (Hasanuddin, 2012). The findings was significant as people nowadays had attached with the internet technology knowledge and it would not be a problem to Muslims to use online payment.